Redesain Jaket Gunung Menggunakan Metode Quality Function Deployment (QFD) - PujiAsih Asih; Siti Lestariningsih; Damar Saloka Anggoro (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2025)
Mountain climbing is an outdoor activity carried out by the Nature Lovers Student Group (MAPALA) as a sporting hobby. One of the equipment that must be brought by climbers is a mountain jacket. The jacket functions to protect the body from strong winds and cold temperatures (00 C). In the market, the most popular jacket demand is a mountain jacket that has a head cover and is splash-proof or waterproof. However, the mountain jacket is still considered less suitable for the needs of mountain climbers, so it is necessary to develop a mountain jacket according to the needs. The purpose of this study is to redesign a mountain jacket according to the needs of climbers, such as a mountain jacket that can protect the face from rain and is not dazzled by sunlight, a comfortable jacket to wear in hot and cold weather, a flexible jacket that can be folded and multi-functional. The method used in this study is Quality Function Deployment where the product planning and development process is structured and can determine the desires and needs of customers to determine product specifications.. The results of this study in the form of a redesign of a mountain jacket according to the priority of consumer desires are that it has a head cover, is not hot or cold when worn. A flexible jacket can be folded or packable and can function as a sleeping bag.